DEPTOR in Skeletal Development and Diseases - Perez-Tejeiro, Jose Miguel; Csukasi, Fabiana (Frontiers in Genetics, 2021)
Discovered only a few years ago, DEP-domain containing mTOR-interacting protein, DEPTOR, is a known regulator of the mechanistic target of Rapamycin (mTOR), an evolutionary conserved kinase that regulates diverse cellular processes in response to environmental stimuli. DEPTOR was originally identified as a negative regulator of mTOR complexes 1 (mTORC1) and 2 (mTORC2), however recent discoveries have started to unravel roles of DEPTOR in mTOR-independent responses. In the past few years, mTOR emerged as an important regulator of skeletal development, growth and homeostasis; dysregulation of its activity contributes to the development of several skeletal diseases, both chronic and genetic. Even more recently, several groups have reported on the relevance of DEPTOR in skeletal biology thorough its action on mTOR-dependent and mTOR-independent pathways. In this review, we summarize the current understanding of DEPTOR in skeletal development and disease